1994
DOI: 10.1007/bf01310566
|View full text |Cite
|
Sign up to set email alerts
|

The coat protein of Indian peanut clump virus: relationships with other furoviruses and with barley stripe mosaic virus

Abstract: The 5'-most open reading frame of the c.4kb RNA-2 of Indian peanut clump furovirus (IPCV) encodes a protein of 208 amino acids. This protein is thought to be the coat protein of IPCV because its amino acid composition and M(r) closely resemble those reported for IPCV coat protein and because its amino acid sequence is 61% identical to that of the coat protein of peanut clump virus (PCV) from West Africa. The extent of the sequence identity between IPCV and PCV coat proteins confirms previous conclusions that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…Transformation of plants with DNA encoding the coat protein and replicase genes of viruses is an efficient means to enhance the germplasm for resistance to viral diseases [19]. The coat protein gene of IPCV from its RNA-2 has been cloned and sequenced [20] and its expression in Nicotiana benthamiana studied [21]. At ICRISAT, attempts are underway to induce resistance to IPCV and other peanut viruses by using biotechnological tools.…”
Section: Introductionmentioning
confidence: 99%
“…Transformation of plants with DNA encoding the coat protein and replicase genes of viruses is an efficient means to enhance the germplasm for resistance to viral diseases [19]. The coat protein gene of IPCV from its RNA-2 has been cloned and sequenced [20] and its expression in Nicotiana benthamiana studied [21]. At ICRISAT, attempts are underway to induce resistance to IPCV and other peanut viruses by using biotechnological tools.…”
Section: Introductionmentioning
confidence: 99%
“…There is some sequence homology among these species for PCV, BSMV and SBWMV, but less with the M r 14000 species of BNYVV. It should also be noted that there is considerable homology between the coat proteins of PCV and BSMV (Wesley et al, 1994). Finally, the three furoviruses possess one feature in common which is not shared with BSMV: the presence on RNA 2 of an additional ORF immediately following the Y-proximal coat protein cistron.…”
Section: Relationships With Other Furovirusesmentioning
confidence: 99%
“…There is a second probable furovirus of groundnut, Indian peanut clump virus (IPCV), which has rod-shaped virions of similar size to those of PCV and an apparently bimodal genome (Reddy et al, 1983). Although PCV and IPCV are not serologically related, recent sequence analysis (Wesley et al, 1994) has revealed that the coat protein of IPCV is 61% identical to that of PCV.…”
Section: Introductionmentioning
confidence: 99%
“…Symptoms on wheat are similar to those caused by SBWMV. However, there is no serological relationship between the two viruses (Reddy et al, 1985) and their genome organization differs substantially (Wesley et al, 1994;Miller et al, 1996;Naidu et al, 1996). The yield reduction in wheat infected with IPCV-H was very severe and consistent over the 3-year period.…”
Section: Discussionmentioning
confidence: 99%